Organizational Capacity Building in Disability Empowerment by UPT Sentra Wirajaya Makassar - Nadia Arimbi Saraswati; Hasniati Hasniati; Muh. Tang Abdullah (Journal La Sociale, 2023)
Capacity Building is a set of activities in which individuals (individuals, organizations, communities, or nation-states) develop the ability to effectively take part in governance. This study aims to see how organizational capacity development has been implemented by UPT Sentra Wirajaya Makassar in terms of disability empowerment in the city of Makassar. The population in this study is employees at the UPT Sentra Wirajaya Makassar Office. Interview guidelines. Data used to be analyzed in a qualitative descriptive manner. The results showed that: 1) Monitor the external environment to identify needs and opportunities for organizational change, has run optimally because UPT sentra wirajaya has been able to develop organizational capacity in terms of monitoring external trends to develop its strategy. 2) Review the organization's strategy, where this strategy works well because the organization has carried out job training that is in direct contact for people with disabilities. 3) Identify capacity needs and plan for capacity development, namely initial monitoring The assessment at this stage has run optimally because it has been deeply carried out by social workers to find out the self-development needs of people with disabilities from various aspects. 4) Negotiate external support forms of external cooperation of the organization have not run optimally to external parties. 5) Implement and manage the capacity development process is already running a good SOP. Where the organization is based on the Constitution on persons with disabilities. 6) Monitor and evaluate the capacity development process Regular monitoring and evaluation of the capacity building process in relation to changes in organizational priorities has been carried out well.